Building critical thinking in pre-service teachers: Dispositions, skills, and standards - İpek Önal (PLoS ONE, 2025)
It is necessary for pre-service teachers to develop their critical thinking dispositions and skills in the pre-service period to develop similar skills in their future students. This research employed a one-group pretest-posttest design to investigate the effect of a 10-week critical thinking training on pre-service teachers’ critical thinking. The training had a significant effect on the development of critical thinking skills. While training led to a significant improvement in critical openness as a sub-dimension of critical thinking disposition, it did not affect critical skepticism. The results revealed significant differences in depth-breadth-adequacy and precision-accuracy dimensions of critical thinking standards.